Prefrontal-hippocampus plasticity reinstated by an enriched environment during stress - Wu, You (2022)
Chronic stress causes dendritic atrophy of neurons within the hippocampus and medial prefrontal cortex. In this report, we show that chronic stress leads to reduced long-term potentiation in the pathway from the hippocampus to the medial prefrontal cortex of rats; and that such reduction is rescued by enriched housing environment. Connectivity between the hippocampus and medial prefrontal cortex is proposed to be an essential substrate that is often compromised in several psychiatric disorders. Our observations suggest that a short period of complexity in the housing environment has the potential to protect the functional integrity of this important connection.